Bauran Pemasaran Sayuran Di Jumbo Pasar Swalayan Manado - Sangaji, Safitri A.; Tambas, Jane Sulinda; Jocom, Sherly Gladys (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The purpose of this study was to identify and analyze the marketing mix of vegetables at Jumbo Pasar Swalayan Manado. This research took place for 4 months starting from July to October 2023. The data used are primary data and secondary data. Primary data is obtained through direct interviews with Jumbo Pasar Swalayan employees and vegetable consumers using a questionnaire. Secondary data is obtained from literature or references related to the research conducted. With a total of 60 respondents. The sampling technique used is accidental sampling. The data analysis used in this research is descriptive analysis. The results showed that Jumbo Pasar Swalayan has implemented 6 aspects of the marketing mix very well including product, price, place, promotion, process, people and physical evidence. However, there is one that is classified as not well implemented, namely the promotion aspect.